Efektivitas Metode Masase Terapi Terhadap Penurunan Kadar Kolesterol - Ahmad Nuruhidin; Satria Armanjaya; Andri Prasetiyo; Redi Setiyadi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The purpose of this study was to determine the effectiveness of massage therapy methods on reducing total cholesterol levels in individuals with hypercholesterolemia. This research method used a quasi-experimental design with a one group pretest-posttest design approach. A total of 10 respondents with cholesterol levels ≥ 200 mg / dL underwent massage therapy for four weeks (twice a week, 30 minutes per session). Cholesterol levels were measured before and after the intervention. Data analysis used the t-test. The results of the study showed that the average cholesterol level before the intervention was 240 mg / dL, decreasing to 180 mg / dL after the intervention. Statistical tests showed significant results with a p value = 0.001 (p <0.05). The conclusion is that massage therapy is effective in lowering total cholesterol levels in individuals with hypercholesterolemia and can be used as a non-pharmacological supporting therapy. Keywords: Hypercholesterolemia, Cholesterol, Massage Therapy